Late Quaternary Palaeoclimate and Contemporary Moisture Source to Extreme NW India: A Review on Present Understanding and Future Perspectives - Sharma, Anupam; Phartiyal, Binita (Frontiers in Earth Science, 2018)
The trans-Himalayan region of NW India along with western part of Tibet, Karakoram,and Hindukush range is hosting thousands of glaciers ensuring perennial freshwater supply to the Indian subcontinent and supporting a large fraction of the global population. The peculiar physiography not only limits the entry of water enriched Indian Summer Monsoon winds to this region but also give passage to dry winds of barren desert of Taklamakan, the Aksai Chin,and western Tibet, making it a cold desert. The Quaternary glacial and interglacial phases govern the present geomorphological setup of the region, wherein the glacial process designed the basic framework, which subsequently modified by the fluvial-lacustrine-aeolian processes.Over the years, our understanding in drawing climatic inferences from the sedimentary archives has improved significantly. However, the discrepancy in chronological results among and within different dating techniques is posing a serious challenge. Since the region is experiencing cold desertic climate and being in the rain shadow zone of the Indian Summer Monsoon (ISM), earlier studies show that the major source of moisture received by the Mediterranean Sea.However, the recent isotopic study of the Indus river water along with other major tributaries and minor streams, it is concluded that ISM source is equally important supplier of the moisture in the Ladakh region of NW India.